The SAGES Manual of Perioperative Care in Minimally Invasive Surgery - Whelan, Richard L.; Fleshman, James W.; Fowler, Dennis L. (Springer New York : Imprint: Springer, 2006)
The perfect execution of a minimally invasive operative technique is only part of the equation for ensuring a favorable surgical outcome. It is also essential to have a complete understanding of the entire spectrum of perioperative care, including preoperative evaluation, technique selection, and postoperative management. Further, it is important to understand the physiologic impact of the C02 pneumoperitoneum. The SAGES Manual of Perioperative Care in Minimally Invasive Surgery provides strategies for successful patient management before, during and after laparoscopic surgery. This easy-to-read manual includes comprehensive and authoritative coverage of perioperative concepts and strategies that not only optimize outcomes but also ensures quality patient care beyond the operating room: guidelines for preoperative evaluation of healthy and complex patients strategies for successful outcomes, including OR setup, patient positioning, anesthetic considerations, exposure technique, port closure method, and hernia prevention multiple port arrangements for most operations and port placement schemes that take into account the B.M.I. of the patient managing trocar placement-related bleeding, prophylaxis against DVT, prevention of intraoperative hypothermia and subcutaneous emphysema when to convert to an open procedure physiologic, immunologic, and oncologic implications of CO2 pneumoperitoneum, prevention of port-site tumors, minimizing the risk of gas embolism postoperative considerations including fluid replacement, ambulation and early postoperative performance criteria The SAGES Manual of Perioperative Care in Minimally Invasive Surgery is written by recognized experts and reflects the Society's commitment to surgical education. .